Literary-Aesthetic Views of the Artist - Khamrakulova Khurshida (Researchparks Publishing, 2021)
The word artist is well aware of the artistic power of the work. The reader also enjoys his views on literature. Because a skilled creator has a deep understanding of what the magic of the word is capable of, how it is acceptable to convey to the reader, the unwritten requirements of creativity. In this sense, it is natural that not only the work of art itself, but also the creative thoughts about the work of art are in the constant focus of the reader.